Improvement of Yttrium Oxyfluoride Coating with Modified Precursor Solution for Laser-Induced Hydrothermal Synthesis - Park, Jaeho; Lee, Kyungwoo; Lee, Jaehong; Hwang, Hae Won; Jeong, Goeen; Kim, Kyung Yeun; Kim, Yu-Chan; Ok, Myoung-Ryul; Han, Hyung-Seop; Sun, Jeong-Yun; Jeon, Hojeong (MDPI AG, 2022)
In the semiconductor manufacturing process, the inner walls of the equipment are coated with yttrium-based oxides for etch resistance against plasma exposure. Yttrium oxyfluoride (YOF) particle synthesis and coating methods have been actively studied owing to their high erosion resistance compared to Y2O3 and Al2O3. Owing to the formation of a rough and porous coating layer by thermal spray-coating, the coating layer disintegrates, as the etching process has been conducted for a long time. Laser-induced synthesis and coating technology offer several advantages, including simplified process steps, ease of handling, and formation of a dense coating layer on the target material. In this study, YOF was coated on an aluminum substrate using a modified precursor solution. The NaF and HMTA were added to the precursor solution, resulting in enhanced synthetic reactivity and stabilizing the oxides. The material coated on the surface was analyzed based on the characteristics of composition, chemical bonding, and phase identification. We found that the coating properties can be improved by using an appropriate combination of modified precursor solutions and laser parameters. Therefore, the findings in this study are expected to be utilized in the field of coating technology.